Monotherapy or combinations? Intravenous vitamin C in sepsis and septic shock: An umbrella review of 31 systematic reviews - Víctor Juan Vera-Ponce; Jhosmer Ballena-Caicedo; Lupita Ana Maria Valladolid-Sandoval; Fiorella E. Zuzunaga-Montoya; Renzo Acosta-Porzoliz; Oriana Rivera-Lozada; Mario J. Valladares-Garrido (PLoS ONE, 2026)
Intravenous (IV) vitamin C has been proposed as an adjuvant therapy in sepsis/septic shock due to its biological plausibility and safety profile, but the proliferation of reviews has not resolved its clinical utility. To synthesize the evidence on IV vitamin C (monotherapy, HAT—hydrocortisone+vitamin C+thiamine—and vitamin C+thiamine) in adults with sepsis/septic shock, prioritizing 28–30-day mortality. Umbrella review of systematic reviews and meta-analyses (MEDLINE/PubMed, Embase, Scopus, and Web of Science, without language restriction). Quality was assessed with AMSTAR 2, overlap with CCA, and when available, TSA and component/network meta-analysis (CINeMA). Certainty of evidence was graded using GRADE with an anchor estimator per outcome and regimen. Thirty-one reviews were included (30 quantitative: 28 SR/MA and 2 component/network MA; 1 qualitative). Combinations (HAT and vitamin C+thiamine) did not reduce mortality; hemodynamic improvements (small decreases in ΔSOFA and vasopressor hours) were modest, did not translate into survival benefits, and were primarily attributable to the corticosteroid. Monotherapy showed a possible mortality benefit signal under specific conditions (initiation ≤24 h, intermediate dose 25–100 mg/kg/day, 3–4-day courses; more pronounced in sepsis than shock), but with low-to-moderate certainty due to heterogeneity, imprecision, publication bias, and very high overlap among reviews. Combination regimens (HAT and vitamin C plus thiamine) did not reduce mortality; hemodynamic improvements were modest, did not translate into survival benefits, and were primarily attributable to the corticosteroid component. For monotherapy, a possible mortality benefit signal was identified under specific conditions (initiation within 24 h, intermediate dose 25–100 mg/kg/day, 3–4-day courses, more pronounced in sepsis than shock), but overall certainty remains low-to-moderate due to heterogeneity, imprecision, publication bias, and very high overlap among reviews. These findings do not support routine use of IV vitamin C in any regimen; for monotherapy, the identified signal warrants rigorous multicenter trials in well-defined clinical scenarios before any recommendation can be made.